The 2021 Cholera Outbreak in West Africa: Epidemiology and Public Health Implications - Sodjinou, Vincent Dossou; Talisuna, Ambrose; Braka, Fiona; Barboza, Phillipe; Alberti, Kathryn; FORTIN, Ann; Kazadi, Walter Mulombo; Anya, Blanche-philomene Melanga; Djingarey, Mamoudou Harouna; Diallo, Binta Fatoumata; et al. (Archives of Clinical and Biomedical Research, 2022)
Introduction: Cholera is one of the most frequent public health emergencies in Sub Saharan Africa. The disease is targeted for elimination by the World Health Organization and the Global Task Force on Cholera Control. Objective: This study describes the 2021 cholera outbreaks in West Africa and determines their public health implication. Method: This was a descriptive cross-sectional study. Non-probability method and exhaustive choice of all countries affected by cholera outbreaks in West Africa in 2021 were performed. Data were collected using line-lists, situation reports, meeting and workshops reports. Results: A total of 108,859 cases and 3,711 deaths (case fatality ratio of 3.4%) were reported from 4 January 2021 to 14 November 2021 in seven countries. The outbreak started on 12 December 2020 in Delta State, Nigeria and was reported later in Benin, Burkina Faso, Cameroon, Mali, Niger and Togo. The global attack rate was 355.7 per 1,000,000 inhabitants and was ranged to 527.2 per 1,000,000 inhabitants in Nigeria. Nigeria was the most affected country with 95% of cases followed by Niger Republic. The outbreak affected 89% of States in Nigeria, 88% of regions in Niger and 58% of departments in Benin. People above 15 years were the most affected (59%) while the under-five accounted for 26% of cases. The sex ratio Female / Male was 1.01 but more deaths were reported within male. The case fatality ratio ranged to 38.5% in Mali. Six countries out of 7 had a case fatality rate above 2%. Low access to safe water and proper sanitation, cross border movements and inadequate behaviors were the main predisposing factors. The magnitude of the outbreaks is unprecedented. The outbreaks were laboratory-confirmed in all the affected countries. Of the 1,086 stool samples col